Effects of Surface Properties on Gastrocnemius Medialis and Vastus Lateralis Fascicle Mechanics During Maximal Countermovement Jumping - Hollville, Enzo; Rabita, Giuseppe; Guilhem, Gaël; Lecompte, Jennyfer; Nordez, Antoine (Frontiers in Physiology, 2020)
The interactions between human movement and surface has previously been studied to understand the influence of surface properties on the mechanics and energetics of jumping. However, little is known about the muscle-tendon unit (MTU) mechanics associated with muscle activity and leg adjustments induced by different surfaces during this movement. This study aimed to examine the effects of three surfaces with different properties (artificial turf, hybrid turf and athletic track) on the muscle mechanics and muscle excitation of the gastrocnemius medialis (GM) and vastus lateralis (VL) during maximal countermovement jumping (CMJ). Twelve participants performed maximal CMJs on the three sport surfaces. GM and VL muscle fascicles were simultaneously imaged using two ultrafast ultrasound systems (500 Hz). MTUs lengths were determined based on anthropometric models and two-dimensional joint kinematics. Surface electromyography (EMG) was used to record GM and VL muscle activity. Surface mechanical testing revealed systematic differences in surface mechanical properties (P = 0.006, η2: 0.26-0.32, large). Specifically, the highest force reduction and vertical deformation values have been observed on artificial turf (65 ± 2 % and 9.0 ± 0.3 mm, respectively), while athletic track exhibited the lowest force reduction and vertical deformation values (28 ± 1 % and 2.1 ± 0.1 mm, respectively) and the highest energy restitution (65 ± 1 %). We observed no significant difference in CMJ performance between the three surfaces ( 35-36 cm, P = 0.66). GM and VL fascicle shortening (P = 0.90 and P = 0.94, respectively) and shortening velocity (P = 0.13 and P = 0.65, respectively) were also unaffected by the type of surface. However, when jumping from greater deformable surface, both GM muscle activity (P = 0.022, η2 = 0.18, large) and peak shortening velocity of GM MTU (P = 0.042, η2 = 0.10, medium) increased during the push-off phase. This resulted in a greater peak plantarflexion velocity late in the jump (P = 0.027, η2 = 0.13, medium). Our findings suggest that maximal vertical jumping task in humans is not affected by common sport surfaces with different mechanical properties. However, internal regulatory mechanisms exist to compensate for differences in surface properties.